Legal Understanding Regarding the Hazards of Drugs in the Framework of Community Development - Sami’an Sami’an (Faculty of Law, Universitas Pekalongan, 2021)
Drug misusse is a danger that is very alarming, because narcotics can damage the individual users, either physically or mentally. Misue and trafficking of narcotics illegally very detrimental to individuals and the wider community, particularly the younger generation, can even pose a greater danger for the life and cultural values of the nation that will ultimately undermine national security. Researchers divide the efforts of drug misuse prevention by the National Narcotics Agency part of the preventive and repressive. Both of these are key functions (operations) in accordance with the duties of the National Narcotics Agency. The misuse of and illicit traffic in narcotic drugs, psychotropic substances and other hazardous materials (drugs) with various implications and the negative impact is a global problem that threatens the life of the community, state and nation. The National Narcotics agency has mengakomidir theory such as that reflected from the division of tasks fields are categorized into the Areas of Prevention and Community Empowerment, Eradication, and Rehabilitation.